Processamento digital e análise estatística de sinais de áudio medidos através de dispositivos móveis para a aplicação no monitoramento do torneamento de ligas de titânio - Porto, Ana Carolina (Universidade Federal de São Carlos, 2023)
When human beings began to organize themselves into society and establish a tasks division, a search for process optimization began. These processes help in the social organization and in the economic growth, na optimization that will be addressed in this paper is monitoring machining processes, with the intention to reduce economic, time and material losses. In this research, an experimental study was carried out to collect data obtained through a mobile device, smartphone, microphone during the turning of a titanium piece in order to verify the mobile devices applicability in monitoring machining processes. The captured sound signals were computationally analyzed in the time and frequency domains, the analysis considered the root mean square (RMS), Discrete Fourier Transform (DFT) and Power Spectral Density (PSD) values of the collected signal. In addition, the study also compared the results obtained through the sound signal with vibration results obtained through an accelerometer in the same experiment, in order to prove or refute the monitoring effectiveness. The results showed that although the analyzed sensor, the smartphone microphone, is not as robust as traditional sensors, it was able to monitor the process, bringing results similar to those obtained with the accelerometer.
Digital processing and statistical analysis of audio signals measured via mobile devices for application in monitoring turning of titanium alloys
Keywords: Monitoramento de processos de usinagem; Torneamento de titânio; Dispositivos móveis em aplicações de engenharia; Processo de sinal sonoro; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO